Manajemen Mutu Terpadu Pada Lembaga Pendidikan Islam Jawa Barat - Aep Tata Suryana; Heri Junaedi; Abubakar Abubakar; Gunawan Gunawan (Center for Research and Community Service (LPPM) University of Abulyatama, 2023)
Total Quality Management (TQM) or Total Quality Management exam literature in the field of education aimed at improving the quality, competitiveness for outputs (graduates) with an indicator of the competence of both intellectual and skill and intelligent mind, spiritual, emotional and balanced between hard skills and soft skills as well as active, creative and innovative and adaptive to the development of science and technology and employment. Integrated quality is not something that happens suddenly and appear before the teachers, employees and the head sekolah.Mutu must direncanakan.Karena there trilogy of quality, namely the quality planning, quality control, and quality improvement. Institutions of Islam that the implications can improve students' competencies that form the civilized man the man who is aware of the rights and obligations to God, on him and on the environment. Integrated Quality Management (TQM) is a management system which utilizes a source - a source of quality in the organization through the stages of management in a controlled manner to improve the quality of service to customers effectively and efficiently.